COMPARISON OF BODY WEIGHT OF LOCAL MALE AND FEMALE SHEEP DUE TO DIFFERENCES IN COMPOSITION BASIC FEED MIXTURE, FERMENTATION CONCENTRATE AND HYACINTH SILAGE - PUTRI ANANDA (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
ABSTRACT Abstract : The purpose of this research is knowing the body weight comparison of male and female local sheep because of the difference in giving mix composition between basal feed, fermented concentrate and water hyacinth silage. This research was conducted for 9 weeks in the Livestock Field Laboratory (LLP) Animal Husbandry Study Program, Faculty of Agriculture, Syiah Kuala University, Rukoh Village, Syiah Kuala District, Banda Aceh City, Aceh Province. This study used a completely randomized design with a factorial pattern consists of 2 factors, namely the gender factor as many as 16 tails consisting of 8 males and 8 females, feed factors P0 (100% basal feed), P1 (80% basal feed + 20% fermented concentrate), P2 (70% basal feed + 10% fermented concentrate + water hyacinth silage 20%), P3 (60% basal feed + concentrate 10% fermentation + 30% water hyacinth silage). Further each treatment consisted of 2 replications. Parameters observed were feed consumption, final body weight, daily body weight gain, feed conversion and feed efficiency.The results showed that the difference in giving mixed composition of basal feed, fermented concentrate and water hyacinth silage very significant effect (P0.01), on the achievement of final body weight, daily body weight gain and feed efficiency in male and female local sheep. However, the treatment of differences in the composition of the mixture between basal feed, fermented concentrate and water hyacinth silage had no significant effect (P0.05) on feed consumption and feed conversion in male and female local sheep.Keywords: comparison, body weight, local sheep, basic feed mixture fermented concentrate, water hyacinth